A novel function of BMHP1 and cBMHP1 peptides to induce the osteogenic differentiation of mesenchymal stem cells. (17th October 2014) - Cao, Feng-Yi; Yin, Wei-Na; Fan, Jin-Xuan; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : BMHP1 or cBMHP1 peptide is found to induce MSCs towards the osteogenic lineage when tethered to modified quartz substrates. Abstract : Bone marrow homing peptide 1 (BMHP1), which was derived from a phage display peptide library (PDPL), is known to be home to bone marrow and bind to stem cells. For the first time, the effect of BMHP1 on the differentiation behavior of mesenchymal stem cells (MSCs) was evaluated. BMHP1 was tethered to modified quartz substrates, and MSCs were seeded on the substrates. It was found that BMHP1 could enhance cell adhesion and proliferation. More importantly, we found that BMHP1 could induce osteogenic differentiation either with a maintenance medium (DMEM) or osteogenic differentiation medium (ODM). Cyclic BMHP1 (cBMHP1) was further synthesized and it was found that cBMHP1 also exhibit a similar, but slightly worse effect on the osteogenic differentiation of MSCs as compared to BMHP1. This work enlightens us on the fact that BMHP1 and cBMHP1 may be used as osteogenic stimulators for MSCs based therapy.